Should I stay or should I go? Gender differences in professional employment - Kathrin Leuze; Alessandra Rusconi (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2009)
Occupational sex segregation is a persistent source of social inequalities. The increasing participation of women in tertiary education and rising female employment rates, however, have given hope that gender inequalities will decline as a result of growing female opportunities for high skill employment in the service sector, e.g. the professions. This paper asks whether such optimistic accounts are justified by comparing male and female professional career trajectories in Germany. Our main assumptions hold that, even today, strong gender differences continue to exist between public and private sector professions, which are further aggravated by different forms of family commitment. Overall, our analyses demonstrate that even among highly qualified men and women, important patterns of sex segregation are present. An initial horizontal segregation between public and private sectors brings about "equal, but different" career prospects, which in the phase of family formation turn into vertical segregation, promoting "different and therefore unequal" labor market chances. – – Berufliche Geschlechtersegregation ist weiterhin eine wichtige Ursache von Geschlechterungleichheiten. Allerdings gibt die zunehmende Beteiligung von Frauen an tertiärer Bildung und am Arbeitsmarkt Anlass zur Hoffnung, dass Geschlechterungleichheiten abnehmen könnten. Denn Frauen haben heute bessere Chancen, in hochqualifizierten Dienstleistungsberufen, sogenannten Professionen, zu arbeiten. Dieser Beitrag fragt, ob solche optimistischen Annahmen berechtigt sind, indem er männliche und weibliche Erwerbstätigkeit in Professionen in Deutschland untersucht. Wir nehmen an, dass auch heute noch stark ausgeprägte Geschlechterunterschiede zwischen Professionen im öffentlichen und privaten Sektor bestehen, die durch geschlechtsspezifische familiäre Verpflichtungen verschärft werden. Unsere empirischen Untersuchungen zeigen, dass auch unter hochqualifizierten Männern und Frauen eine hohe Arbeitsmarktsegregation existiert. Eine anfänglich horizontale Segregation zwischen dem öffentlichen und privaten Sektor bewirkt einen "gleichen, aber unterschiedlichen" Berufseinstieg. Zu dieser horizontalen Segregation kommt in der familienintensiven Phase eine vertikale Segregation hinzu, was "unterschiedliche und dadurch ungleiche" Arbeitsmarktchancen von Männern und Frauen begünstigt.
Keywords: 300; professions; sex segregation; labor market outcomes; family formation; tertiary education; Germany; Professionen; Geschlechtersegregation; Arbeitsmarkterträge; Familienbildung; tertiärer Bildungsbereich; Deutschland